2022
DOI: 10.3389/fpsyg.2022.999750
|View full text |Cite
|
Sign up to set email alerts
|

Men’s reactions to gender inequality in the workplace: From relative deprivation on behalf of women to collective action

Abstract: Over recent years, the role of men as women’s allies in the struggle for gender equality has become increasingly important. Previous research has shown that often men do not fight gender inequalities as they fail to recognize the severity of discrimination against women (e.g., in hiring). In this study (N = 427), we examined whether men who experienced relative deprivation on behalf of women—a form of relative deprivation that stems from the awareness that women hold a less privileged position in society—were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…In Italy, where the study was conducted, traditional gender stereotypes and patriarchy are still pervasive (e.g., ISTAT, 2019 ; Pagliaro et al, 2020 ; Mazzuca et al, 2022 ). In such a context, it seems likely that women who are aware of male domination—as most women in our sample—might easily identify patriarchal culture as a critical threat to them as well as to other groups accused of undermining traditional values or who openly fight against patriarchy, such as LGBTQIA+ people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Italy, where the study was conducted, traditional gender stereotypes and patriarchy are still pervasive (e.g., ISTAT, 2019 ; Pagliaro et al, 2020 ; Mazzuca et al, 2022 ). In such a context, it seems likely that women who are aware of male domination—as most women in our sample—might easily identify patriarchal culture as a critical threat to them as well as to other groups accused of undermining traditional values or who openly fight against patriarchy, such as LGBTQIA+ people.…”
Section: Discussionmentioning
confidence: 99%
“…Group relative deprivation has been related to a greater willingness to act for social change (Smith et al, 2012 ; Agostini and van Zomeren, 2021 ; see also Mazzuca et al, 2022 ) but also to more negative attitudes toward outgroups (Moscatelli et al, 2014 ; Anier et al, 2016 ). Pettigrew et al ( 2008 ), analyzing data from different European countries, showed that the more individuals reported feelings of being relatively deprived as citizens of their countries, the more they exhibited prejudice against immigrants.…”
Section: Introductionmentioning
confidence: 99%
“…Men with more knowledge about gender inequities at their institution are more likely to actively support efforts to advance women. 56 …”
Section: Encourage Equal Opportunity To Attain Career Milestonesmentioning
confidence: 99%
“… 61 63 Research on factors that encourage or discourage an early career woman from choosing a leadership path could identify strategies to recruit talented women into leadership and, if needed, adjust the existing and future leadership environment to be more welcoming to women. Although some research has been conducted on encouraging men to take action against gender inequity, 56 , 64 effectively shifting the culture of academic medicine toward equity will require focused work on creating shared ownership among leaders of all genders with longitudinal outcomes. These efforts should also include supporting URiM faculty.…”
Section: Future Directions For Researchmentioning
confidence: 99%